Strategi Kepala Sekolah dalam Implementasi Pendidikan Karakter di Sekolah Menengah Kejuruan - Sihabudin; Mochamad Asep Kuswara (South Sulawesi Education Development (SSED), 2025)
The issue of weak implementation of character education at SMK Muhammadiyah Lemahabang, Cirebon Regency, is reflected in student behaviors inconsistent with moral and religious values, such as low discipline and negative environmental influences. This study aims to analyze the principal’s strategies in implementing character education, identify supporting and inhibiting factors, and evaluate the success of the implemented programs. This research employs a qualitative method with library and field approaches. Data were collected through in-depth interviews with the principal, teachers, and students, along with document analysis such as school policies and evaluation reports. Direct observations of routine school activities were conducted to understand the applied character education strategies. The data were descriptively analyzed to provide a systematic overview of the program’s implementation. The results reveal that the principal's strategies include integrating religious values into routine activities such as prayer recitation, Qur’an reading, congregational prayers, and programs like BTQ (Reading and Writing the Qur’an) and Qur’an memorization. Supporting factors include the principal's commitment, parental and community support, and adequate infrastructure. Main obstacles involve limited time, negative environmental influences, and the presence of stalls near the school. Evaluations indicate improvements in students' religiosity and discipline, although strengthening control over the external environment is necessary. Character education programs should be optimized with better time management and stronger collaboration with the community.